2006
DOI: 10.1161/01.hyp.0000201540.91234.8f
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Effects of Hydrogen Peroxide in Arteries and Veins From Normotensive and Hypertensive Rats

Abstract: Hydrogen peroxide causes vascular contraction and relaxation and contributes to the pathogenesis of hypertension. We hypothesized that the contractile state of blood vessels governs whether H2O2 causes contraction or relaxation. Hydrogen peroxide (1 micromol/L to 1 mmol/L) concentration-dependently contracted thoracic aorta and vena cava from sham normotensive and deoxycorticosterone acetate (DOCA)-salt hypertensive rats. The maximal contraction to H2O2 was 3 times greater in DOCA aorta compared with sham aort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 28 publications
0
28
0
5
Order By: Relevance
“…In support of this, contraction of rat aorta by hydrogen peroxide was attenuated by the removal of extracellular Ca 2ϩ . 31) However, the L-type Ca 2ϩ channel antagonist, nicardipine, did not inhibit sustained contraction induced by the purine and XOD system, indicating that ROS stimulates other type(s) of Ca 2ϩ channel directly and/or activates signaling cascades which affect Ca 2ϩ influx indirectly.…”
Section: Fig 5 Inhibitory Effects Of Various Ros Scavengers On Dysfmentioning
confidence: 92%
“…In support of this, contraction of rat aorta by hydrogen peroxide was attenuated by the removal of extracellular Ca 2ϩ . 31) However, the L-type Ca 2ϩ channel antagonist, nicardipine, did not inhibit sustained contraction induced by the purine and XOD system, indicating that ROS stimulates other type(s) of Ca 2ϩ channel directly and/or activates signaling cascades which affect Ca 2ϩ influx indirectly.…”
Section: Fig 5 Inhibitory Effects Of Various Ros Scavengers On Dysfmentioning
confidence: 92%
“…It has been suggested that differences in the K + channel and/or Ca 2+ handling in various vascular beds or under different conditions may mediate these diverse actions of H2O2. In hypertensive rats, there is an increase in H2O2-induced contraction in arteries but not in veins, 18 and plasma H2O2 levels have been shown to correlate with mean arterial pressure in hypertensive patients. Overall, these findings suggest a role of ROS in vascular function and blood pressure regulation.…”
Section: (-S -) Thiyl Radical (-S · ) Disulfides (-S-s-) Disulfidementioning
confidence: 97%
“…Several prohypertensive effects have been described for H2O2, such as increased vasoconstriction, vascular hypertrophy and hyperplasia, decreased diuresis and natriuresis and also increased spinal sympathetic outflow [7,50,[52][53][54][55][56][57][58]. Increasing evidence has also shown that H2O2 amplifies oxidative stress by stimulating ROS generation by NADPH oxidases, XO and eNOS [7,51].…”
Section: Rnsmentioning
confidence: 99%